Liberty, governance and resistance : competing discourses in John Locke's political philosophy - Tate, John William (New York, NY : Routledge, 2024)
"John Locke is widely perceived as a foundational figure within the liberal tradition. This book investigates the competing purposes that informed Locke's political philosophy, not all of which resulted in outcomes consistent with what we today understand as "liberal" ideals. Locke himself was unaware that he belonged to a "liberal" tradition. Traditions only acquire meaning in retrospect. But many have perceived the development of Locke's political philosophy as involving a smooth evolution from "authoritarian" origins to "liberal" conclusions, beginning with Locke's Two Tracts on Government (1660-62) and culminating in his later political works, the Two Treatises of Government (1689) and A Letter Concerning Toleration (1689). This book advances an interpretation of this development which reveals how, by the time of his mature political writings, Locke sought to advance three competing imperatives within his political philosophy, only two of which were consistent with ideals of individual liberty. The other imperative sustained purposes much more aligned with the "authoritarianism" with which Locke's political philosophy began. The result is a much more complex and variegated understanding of Locke's political philosophy, focusing on its competing purposes. Liberty, Governance and Resistance will be of interest to researchers studying Locke, liberalism, and the history of ideas"--
Two tracts on government -- An essay concerning toleration -- Two treatises of government -- Locke, liberty and consent -- Upheaval and disorder -- "Busie Heads" and "Turbulent Spirits" -- The Locke literature.
Keywords: Locke, John, -- 1632-1704 -- Political and social views; Liberalism -- History -- 17th century; Political science -- Philosophy -- History -- 17th century; PHILOSOPHY / Political; POLITICAL SCIENCE / Political Ideologies / Conservatism & Liberalism